Evaluating hematological and inflammatory biomarkers in tuberculosis management - Sanatkumar Bharamu Nyamagoud; Princy Domnic Dsouza; Sai Phalguna Prakash Chitralu; Kadambari Solankure; Agadi Hiremath Viswanatha Swamy (Monaldi Archives for Chest Disease)
Tuberculosis (TB) remains a significant public health concern, particularly in resource-limited settings. Accurate and timely diagnosis and effective monitoring of disease progression and treatment response remain a challenge. This research aims to evaluate the function of hematological and inflammatory biomarkers, including hemoglobin (HB), serum amyloid A (SAA), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and white blood cell (WBC) count, in TB patients. Overall, 80 TB patients were analyzed to evaluate the association of these biomarkers with disease status and demographic characteristics. The findings revealed significant alterations in inflammatory markers, with elevated WBC, SAA, CRP, and ESR levels, indicating an ongoing inflammatory response. Additionally, decreased HB levels were observed, suggesting the presence of anemia, which is commonly associated with chronic infections such as TB. Pearson's correlation analysis revealed a significant negative connection between HB and inflammatory markers, reinforcing the link between anemia and TB-associated inflammation. However, no noteworthy associations were found between biomarker levels and demographic parameters, including age and gender, residence, or treatment duration. These findings emphasize the potential utility of these biomarkers in TB diagnosis, prognosis, and treatment monitoring, especially in regions where advanced diagnostic tools are not readily available. The study suggests that routine hematological and inflammatory markers can serve as cost-effective adjunctive tools in TB administration. Additional investigation is needed to confirm these results and determine their role in predicting treatment outcomes and disease severity.